IKHTILAF AL-MUFASSIRIN: MEMAHAMI SEBAB-SEBAB PERBEDAAN ULAMA DALAM PENAFSIRAN ALQURAN - Ahmad Zainal Abidin (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2019)
All Muslims agree that the Qur’an is the first and main source of Islamic law. Nevertheless, this scripture does not guarantee the same result of interpretation, given that the background of life surrounding of the interpreter is different. This paper will review the forms of ikhtilaf al-mufassirin and the causes that bring it up. In examining the causes of ikhtilaf al-mufassirin, there are at least two causes; (1) a common cause, such as the occurrence of ikhtilaf in the case of qira’at, i’rab, musytarak, hakakat-majaz, ‘am-khas, mutlaq-muqayyad, mujmal-mubayyan, amr-nahi, nasikh-mansukh, and ikhtilaf in positioning reason as the source of shari’a law; (2) special causes, such as ikhtilaf in criticism of sanad and matan, ikhtilaf in taking a source of law, and ikhtilaf in the case of aqidah and madhhab. While the forms of ikhtilaf al-mufassirin there are also two forms; (1) ikhtilaf tanawwu’, ie dissent of opinion which is all aimed at the same intention; (2) ikhtilaf taddad, that is, differences of opinion which is conflicting and can not be united.